2016
DOI: 10.1038/eye.2016.185
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular endothelial function and severity of primary open angle glaucoma

Abstract: PurposeThe role of microvascular endothelial dysfunction on severity of primary open angle glaucoma (POAG) was investigated in this study.Patients and methodsA prospective cohort study was conducted. One hundred and fourteen ethnically Malay patients (114 eyes) with POAG treated at the eye clinic of Hospital University Sains Malaysia between April 2012 and December 2014 were recruited. Patients aged between 40 and 80 years with two consecutive reliable and reproducible Humphrey visual field 24-2 analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Elevated serum levels of ET-1 and other biochemical markers of endothelial function in the aqueous humor of glaucoma patients suggest that endothelial dysfunction is associated with disease pathology (Sugiyama et al, 1995;Noske et al, 1997;Resch et al, 2009a;Ghanem et al, 2011;Cellini et al, 2012;Li et al, 2016). There is a statistically significant correlation between microvascular endothelial function and severity of POAG in the Malay population (Bukhari et al, 2016). In patients, blocking both ET A and ET B receptors results in increased blood flow through the retina, choroid and ONH.…”
Section: Blood Flow Regulation Is Impaired In Glaucomamentioning
confidence: 99%
“…Elevated serum levels of ET-1 and other biochemical markers of endothelial function in the aqueous humor of glaucoma patients suggest that endothelial dysfunction is associated with disease pathology (Sugiyama et al, 1995;Noske et al, 1997;Resch et al, 2009a;Ghanem et al, 2011;Cellini et al, 2012;Li et al, 2016). There is a statistically significant correlation between microvascular endothelial function and severity of POAG in the Malay population (Bukhari et al, 2016). In patients, blocking both ET A and ET B receptors results in increased blood flow through the retina, choroid and ONH.…”
Section: Blood Flow Regulation Is Impaired In Glaucomamentioning
confidence: 99%
“…Compared to normal subjects, glaucoma patients exhibit blood flow abnormalities in vessels of the optic nerve head, 18 retina, 18 retrobulbar tissue, 19 and choroid. 18 , 20 , 21 With limited information regarding autonomic dysfunction involvement, several researchers proposed that ocular vessel disturbances are linked to plasma levels of endothelin-1, 22 systemic blood pressure, 23 , 24 and vasospasm. 25 Autonomic function reflects the effect of parasympathetic nervous system activity on the heart.…”
mentioning
confidence: 99%
“…In the current study, we observed endothelial dysfunction of retinal arterioles and structural changes in retinal tissue of I/R-treated pigs. Recent studies have been more and more focused on the association between endothelial dysfunction and the severity of vision-threatening diseases like primary open angle glaucoma and diabetic retinopathy due to the important role of an intact endothelium for proper regulation of retinal perfusion [26,27,28]. In the present study, retinal arteriole dilation after I/R was blunted in response to the endothelium-dependent vasodilator, bradykinin, but not to the endothelium-independent vasodilator, SNP, indicative of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%